Transepithelial delivery of insulin conjugated with phospholipid-mimicking polymers via biomembrane fusion-mediated transcellular pathways. (1st March 2022) - Hatano, Hiroaki; Meng, Fanlu; Sakata, Momoko; Matsumoto, Akira; Ishihara, Kazuhiko; Miyahara, Yuji; Goda, Tatsuro
Abstract: Epithelial barriers that seal cell gaps by forming tight junctions to prevent the free permeation of nutrients, electrolytes, and drugs, are essential for maintaining homeostasis in multicellular organisms. The development of nanocarriers that can permeate epithelial tissues without compromising barrier function is key for establishing a safe and efficient drug delivery system (DDS). Previously, we have demonstrated that a water-soluble phospholipid-mimicking random copolymer, poly(2-methacryloyloxyethyl phosphorylcholine30 - random - n ‑butyl methacrylate70 ) (PMB30W), enters the cytoplasm of live cells by passive diffusion manners, without damaging the cell membranes. The internalization mechanism was confirmed to be amphiphilicity-induced membrane fusion. In the present study, we demonstrated energy-independent permeation of PMB30W through the model epithelial barriers of Madin-Darby canine kidney (MDCK) cell monolayers in vitro . The polymer penetrated epithelial MDCK monolayers via transcellular pathways without breaching the barrier functions. This was confirmed by our unique assay that can monitor the leakage of the proton as the smallest indicator across the epithelial barriers. Moreover, energy-independent transepithelial permeation was achieved when insulin was chemically conjugated with the phospholipid-mimicking nanocarrier. The bioactivity of insulin as a growth factor was found to be maintained even after translocation. These fundamental findings may aid the establishment of transepithelial DDS with advanced drug efficiency and safety. Statement of significance: A nanocarrier that can freely permeate epithelial tissues without compromising barrier function is key for successful DDS. Existing strategies mainly rely on paracellular transport associated with tight junction breakdown or transcellular transport via transporter recognition-mediated active uptake. These approaches raise concerns about efficiency and safety. In this study, we performed non-endocytic permeation of phospholipid-mimicking polymers through the model epithelial barriers in vitro . The polymer penetrated via transcytotic pathways without breaching the barriers of biomembrane and tight junction. Moreover, transepithelial permeation occurred when insulin was covalently attached to the nanocarrier. The bioactivity of insulin was maintained even after translocation. The biomimetic design of nanocarrier may realize safe and efficient transepithelial DDS. Graphical abstract: Image, graphical abstract